PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN DI SWISS-BELINN LEGIAN HOTEL - I Gusti Ngurah Sugita; I Wayan Arta Artana; I Gusti Nyoman Wiantara (Journal of Tourism and Interdiciplinary Studies, 2021)
This research aims to identify the affect of each dimension of service quality toward level of guests’ satisfactions at Swiss-Belinn Legian Hotel. Research methods used in this research including observation, interview, survey and literature review. A total of 90 guests in house as the population who surveyed to response the questionare. The instrument was tested using validity test, reliability test, classic assumption tests then data analyzed using linier regression, T test and F test. Based on the analysis it is found that partially the reliability, responsiveness, assurance, empathy dan tangible variables affect guests’ satisfactions at Swiss-Belinn Legian Hotel positively and significantly. This can be seen from the T test wherein the t-test of reliability variable (8,891) > t-table (1,6), t-test of responsiveness variable (8,879) > t-table (1,6), t-test of assurance variable (6,585) > t-table (1,6), t-test of empathy variable (5,163) > t-table (1,6) and t-test of tangible variable (4,478) > t-table (1,6). Simultaneously, the reliability, responsiveness, assurance, empathy and tangible variables affect guests’ satisfactions at Swiss-Belinn Legian Hotel positively. This can be seen form the F test wherein f-test (92,140) > f-table (2,3). The percentage of effect of reliability, responsiveness, assurance, empathy and tangible variables toward guests’ satisfactions is 84,6% which is proven with R square which constitute 0,846. Among the five independent variables used in this research, responsiveness has the most dominant affect toward guests’ satisfactions as shown on the coefficient beta (ß) X3= 0,968 > X1=0,247, X2=0,477, X4=0,313, X5=0,262.